Knowledge of Mothers and Anemia Status of Stunting Children at Oepoi Community Health Center - Valeria Saubaki; Wilhelmus Olin; Yoan Novicadlitha; Retno Martini Widhyasih (Laboratory Journal of Infectious Diseases, 2025)
Anemia is a significant factor contributing to stunting, affecting maternal capabilities in childcare, including energy levels and breast milk quality. This descriptive quantitative study was conducted at the Nyiur and Seroja integrated service posts within the Oepoi Community Health Center in Kupang City. Total sampling was employed, involving 44 respondents comprising mothers and children diagnosed with stunting. Among child respondents, 12 (55%) were male and 10 (45%) were female. The most represented age group was >2–3 years (15 samples, or 68,18%), while the >3–5 years group had 7 samples (31,81%). Hemoglobin levels indicated that 8 children (36%) were in the abnormal range, while 14 (64%) were normal. All maternal respondents (22 samples, 100%) were aged 20 years and above. Maternal knowledge assessment revealed that 13 respondents (59,09%) had good knowledge, while 9 (40,91%) had poor knowledge regarding anemia. These findings highlight the notable prevalence of anemia among mothers and children in the study area, emphasizing the need for targeted interventions to address this issue, as it significantly impacts child health and development. Addressing anemia in mothers and children is crucial to combat stunting and improve overall health outcomes in the community.